A New Look at Firm Market Value, Investment, and Adjustment Costs - Barnett, Steven A.; Sakellaris, Plutarchos (The Review of Economics and Statistics, 1999)
We demonstrate that the conventional practice of running firm investment regressions on beginning-of-period average Q cannot recover structural parameters related to adjustment costs. We propose two new methods of estimating these structural parameters by using financial market information (average Q's). We find that the sensitivity of investment to Q is more than ten times higher than estimated in conventional Q regressions. Furthermore, a firm's investment rate is more responsive to expected future Q the higher the level of this Q; i.e., investment is a convex function of fundamentals. The cost of installing new capital is estimated to be approximately 10% to 13% of the total investment cost (including purchase) at usual rates of investment.